1994
DOI: 10.1002/jgt.3190180210
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of the smallest eigenvalue of a graph

Abstract: It is well known that the smallest eigenvalue of the adjacency matrix of a connected d‐regular graph is at least − d and is strictly greater than − d if the graph is not bipartite. More generally, for any connected graph G = (V, E), consider the matrix Q = D + A where D is the diagonal matrix of degrees in the graph G and A is the adjacency matrix of G. Then Q is positive semidefinite, and the smallest eigenvalue of Q is 0 if and only if G is bipartite. We will study the separation of this eigenvalue from 0 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 6 publications
0
88
0
Order By: Relevance
“…The matrix D + A is called the signless Laplacian in [16], and it appears very rarely in published papers (see [5]), the paper [13] being almost the only relevant research paper published before 2003. Only recently has the signless Laplacian attracted the attention of researchers [4,8,11,10,16,26].…”
Section: (L(g)) + 2i Where D Is the Diagonal Matrix Of Vertex Degreementioning
confidence: 99%
See 1 more Smart Citation
“…The matrix D + A is called the signless Laplacian in [16], and it appears very rarely in published papers (see [5]), the paper [13] being almost the only relevant research paper published before 2003. Only recently has the signless Laplacian attracted the attention of researchers [4,8,11,10,16,26].…”
Section: (L(g)) + 2i Where D Is the Diagonal Matrix Of Vertex Degreementioning
confidence: 99%
“…The parameter ψ was introduced in [13] as a measure of non-bipartiteness. It is shown that the least eigenvalue q n of the signless Laplacian Q is bounded above and below by functions of ψ.…”
Section: Basic Properties Of Q-spectramentioning
confidence: 99%
“…The matrix L = D − A is known as the Laplacian of G and has been studied extensively in literature (see, e.g., [1]). The matrix Q = D + A is called the signless Laplacian in [4] and appears very rarely in published papers (see [1]), the paper [2] being one of the very few research papers concerning this matrix. Since the signless Laplacian is a positive semi-definite matrix, all its eigenvalues are non-negative.…”
Section: Introductionmentioning
confidence: 99%
“…First, we show that the sequences of the moduli of (signless) Laplacian coefficients of graphs are log-concave, and hence unimodal. As a consequence, we obtain some lower and upper bounds on the algebraic connectivity and the least eigenvalue of the signless Laplacian matrix, which is studied in [7] as a measure of non-bipartiteness of a graph. Moreover, we obtain upper bounds for the partial sums of the Laplacian eigenvalues.…”
Section: Elamentioning
confidence: 99%
“…In other words, we have Let η denote the nullity of the matrix Q(G). The following theorem explicitly expresses the connection between η and the structure of G. In [7], the least eigenvalue of Q(G) was studied as a measure of non-bipartiteness of a graph. Here, we obtain a lower bound for this quantity.…”
Section: Elamentioning
confidence: 99%